ANALISIS FLEKSIBILITAS REPRESENTASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL HIMPUNAN DITINJAU DARI GAYA BELAJAR KOLB - Annisa Ardana Herawati; Abdussakir Abdussakir (Universitas Bhinneka PGRI, 2025)
The ability to flexibly use mathematical representations is a crucial aspect of mathematics learning, particularly in solving problems through intra- and inter-representational transformations. However, the influence of learning styles on representational flexibility remains underexplored. This study aims to analyze students' mathematical representational flexibility in solving set problems based on Kolb's learning styles (Accommodator, Assimilator, Diverger, and Converger). A descriptive qualitative approach was employed, involving 12 eighth-grade students selected through a Kolb learning style questionnaire. Data were collected using a mathematical representation flexibility test, semi-structured interviews, and documentation. The research instruments included test sheets and interview guidelines, analyzed using the Miles and Huberman model. The findings revealed that Accommodator students excel in recognition and treatment but are limited in conversion, while Assimilator students demonstrate high flexibility in conversion. Diverger students are strong in recognition, whereas Converger students show excellent initial visualization but need reinforcement in treatment. Teachers are encouraged to implement learning strategies tailored to student's learning styles to enhance their representational flexibility. Future research should explore other mathematical topics or different educational levels.